Effects of conversation content on viewing dyadic conversations - Jarkko Hautala; Otto Loberg; Jari K Hietanen; Lauri Nummenmaa; Piia Astikainen (Journal of Eye Movement Research)
People typically follow conversations closely with their gaze. We asked whether this viewing is influenced by what is actually said in the conversation and by the viewer’s psychological condition. We recorded the eye movements of healthy (N = 16) and depressed (N = 25) participants while they were viewing video clips. Each video showed two people, each speaking one line of dialogue about socio-emotionally important (i.e., personal) or unimportant topics (matter-of-fact). Between the spoken lines, the viewers made more saccadic shifts between the discussants, and looked more at the second speaker, in personal vs. matter-of-fact conversations. Higher depression scores were correlated with less looking at the currently speaking discussant. We conclude that subtle social attention dynamics can be detected from eye movements and that these dynamics are sensitive to the observer’s psychological condition, such as depression.